2016
DOI: 10.5478/msl.2016.7.4.000
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Glycerol with Isolation of Endogenous Interferences using "Dilute and Shoot" Strategy and High-Resolution Mass Spectrometry in Human Urine for Antidoping Testing

Abstract: : Glycerol was identified and isolated from endogenous interferences during analysis of human urine using high-resolution mass spectrometry (HRMS) for doping control. Urinary sample preparation was simple; the samples were diluted with an organic solvent and then analyzed using a liquid chromatography-mass spectrometry ("dilute and shoot" method). Although the interfering ion peaks were observed at the similar retention time of glycerol, the inference could be identified by isolation with HRMS and further inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…regulates the identification of meldonium dihydrate by absorption spectrophotometry in the IR range and quantitative determination by acidimetric in a non-aqueous medium with potentiometric fixation of the titration point [5]. After conducting a review of scientific literature regarding the existing methods of meldonium analysis, it has been shown that there is only one spectrophotometric method [6] and numerous chromatographic methods [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] for the determination of meldonium in substances, pharmaceuticals and biological fluids. The spectrophotometric determination of meldonium in medicines had been proposed by a scientific group from the ZSMU under the leadership of prof. S. O. Vasyuk was based on the formation of a coloured reaction product of meldonium with p-chloranil in dimethylformamide (DMF) medium with an absorption maximum at a wavelength of 556 nm.…”
Section: Introductionmentioning
confidence: 99%
“…regulates the identification of meldonium dihydrate by absorption spectrophotometry in the IR range and quantitative determination by acidimetric in a non-aqueous medium with potentiometric fixation of the titration point [5]. After conducting a review of scientific literature regarding the existing methods of meldonium analysis, it has been shown that there is only one spectrophotometric method [6] and numerous chromatographic methods [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] for the determination of meldonium in substances, pharmaceuticals and biological fluids. The spectrophotometric determination of meldonium in medicines had been proposed by a scientific group from the ZSMU under the leadership of prof. S. O. Vasyuk was based on the formation of a coloured reaction product of meldonium with p-chloranil in dimethylformamide (DMF) medium with an absorption maximum at a wavelength of 556 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Meldonium dihydrate is described in the European Pharmacopoeia [4,5]; for assay of meldonium, European Pharmacopoeia proposes acidimetric non-aqueous titration. By surveying the literature review, it was found that numerous methods have been reported for the determination of meldonium in biological fluids [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and food products [22], but only a few methods have been reported for the determination of medonium in dosage forms medicines [23][24][25][26]. Meldonium dehydrates (Fig.…”
Section: Introductionmentioning
confidence: 99%